1972
DOI: 10.1113/jphysiol.1972.sp009760
|View full text |Cite
|
Sign up to set email alerts
|

Changes during eating in oxygen consumption, cardiac function and body fluids of sheep

Abstract: 3. Arterial Po. did not change significantly during eating. However PV 02 fell slightly but significantly. The 02 saturation of venous blood fell due to the decline in pH. Estimated CO2 in arterial blood increased as a consequence of increased haemoglobin content. The net effect was to increase arteriovenous difference in 02 content from 4-4 ml./100 ml. before eating to 6-0 ml./100 ml. at the end of the meal.4. 02 consumption increased about 60 % during eating and fell rapidly thereafter. Heart rate followed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
3

Year Published

1975
1975
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 18 publications
1
22
3
Order By: Relevance
“…Fasting plus water restriction in the warm environment resulted in an increase of blood haemoglobin after 24 h of treatment (P < 0.05). The blood haemoglobin values (11.58-13.22 g dL -1 ) in the present investigation were higher than values (8-9 g dL -1 ) reported by (Christopherson and Webster 1972) for mature ewes. The difference could have been a result of age and nutritional conditions in the two studies.…”
Section: Haemoglobincontrasting
confidence: 55%
See 1 more Smart Citation
“…Fasting plus water restriction in the warm environment resulted in an increase of blood haemoglobin after 24 h of treatment (P < 0.05). The blood haemoglobin values (11.58-13.22 g dL -1 ) in the present investigation were higher than values (8-9 g dL -1 ) reported by (Christopherson and Webster 1972) for mature ewes. The difference could have been a result of age and nutritional conditions in the two studies.…”
Section: Haemoglobincontrasting
confidence: 55%
“…The present treatments resulted in only 3.4-7.0% losses of plasma volume. These were less than data from Degen and Kam (1992), which showed that rams lost 41.7% plasma volume after deprivation of water for 4 d. These differences may be due to different methods of assay and calculation, ability of adaptation to dehydration as inherited differences, or due to feeding conditions (Christopherson and Webster 1972).…”
Section: Plasma Volumecontrasting
confidence: 39%
“…The 11 % reduction in plasma volume was similar to values for reductions in plasma volume and thiosulphate space reported by others (Ternouth 1968;Blair-West and Brook 1969;Christopherson and Webster 1972). Maximum haematocrit in the present study coincided in each case with the occurrence of minimum plasma volume.…”
Section: Discussionsupporting
confidence: 72%
“…The physiology of sheep is extensively altered when they start to eat dry rations (Blair-West and Brook 1969;Christopherson and Webster 1972;Dooley et al 1972). Several of the observed changes may be related directly to the need of the sheep under these feeding conditions to produce large volumes of saliva rapidly to facilitate swallowing.…”
Section: Introductionmentioning
confidence: 99%
“…The events that take place during and immediately after the act of eating, in particular the passage of plasma fluid to extracellular space and then to the digestive tract (Bailey 1961;Stacy and Warner [1966] cited in Christopherson and Webster [1972]) and the increase of osmotic pressure (Stacy and Warner [1966] cited in Christopherson and Webster [1972]; Ternouth 1968) could possibly explain a parallel movement of ALB from intravascular to extravascular space, to prevent abrupt and dangerous variations of oncotic pressure. Since the permeability of vascular walls to ALB is low, movement of ALB probably occurs mainly across the large pores of the liver sinusoids.…”
Section: Albumin Globulins and Total Proteinmentioning
confidence: 99%